Solid electrolyte base material, solid electrolyte, secondary battery, and method for manufacturing solid electrolyte base material
Patent Information
- Application Number
- JP2023148390
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0013】 本開示の少なくとも一つの態様によれば、イオン電導度が大きく、短絡が抑制された固体電解質を得るための、取り扱いが容易な固体電解質基材が提供される。
Smart Images

Figure 2025041222000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a solid electrolyte substrate, a solid electrolyte, a secondary battery, and a method for producing a solid electrolyte substrate. [Background technology]
[0002] In general, secondary batteries are composed of electrodes (positive and negative electrodes) and an electrolyte, and are charged and discharged by the movement of ions between the electrodes via the electrolyte. Such secondary batteries are used in a wide range of applications, from small devices such as mobile phones to large devices such as electric vehicles. Therefore, there is a demand for further improvement in the performance of secondary batteries.
[0003] In recent years, research and development of so-called all-solid-state batteries, which use inorganic solid electrolytes as electrolytes, has progressed. All-solid-state batteries are expected to improve the safety and capacity and output of secondary batteries by replacing conventional organic electrolytes with solid electrolytes. When inorganic solid electrolytes are used in secondary batteries, the contact resistance is large compared to liquid electrolytes, so the ionic conductivity tends to be low and short circuits are more likely to occur.
[0004] In order to solve such problems, Patent Document 1 discloses an all-solid-state battery obtained by laminating a solid electrolyte sheet, which is prepared by applying a solid electrolyte slurry to a PET film and drying the film, on an active material to obtain a laminate, and then subjecting the laminate to a heat treatment. Furthermore, Patent Document 2 discloses a method for producing a solid battery material in which a solid electrolyte powder is used as a starting material, and then the solid electrolyte layer can be formed in a compacted powder form by uniformly filling the powder with a desired thickness and pressing it. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-212022 A [Patent Document 2] JP 2012-221887 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, according to the study by the present inventors, when the slurry for the solid electrolyte is applied to a PET film and dried as in Patent Document 1, the thickness of the coating layer of the solid electrolyte after drying is as thick as 250 μm, and the ion conductivity of the solid electrolyte is insufficient. Also, as in Patent Document 2, the pressed powder-like solid electrolyte layer having a thickness of about 50 μm to 60 μm is brittle and difficult to handle, and is not suitable for practical use. Therefore, an object of the present disclosure is to provide an easy-to-handle solid electrolyte base material for obtaining a solid electrolyte having high ionic conductivity and suppressed short circuits. [Means for solving the problem]
[0007] According to at least one embodiment of the present disclosure, there is provided a solid electrolyte substrate for use in the production of a solid electrolyte, comprising: The base and a first particle portion elastically held to the base by an adhesive; a second particle portion including a compact of solid electrolyte particles stacked and held on the first particle portion; A solid electrolyte substrate having a
[0008] According to at least one embodiment of the present disclosure, a solid electrolyte base material used in the production of a solid electrolyte The material is The base and a layer of adhesive on the base; a first particle portion dispersed and held in the adhesive; a second particle portion including a compact of solid electrolyte particles stacked and held on the first particle portion; A solid electrolyte substrate having a
[0009] According to at least one embodiment of the present disclosure, there is provided a solid electrolyte obtained by removing at least a portion of the base from the solid electrolyte substrate.
[0010] According to at least one embodiment of the present disclosure, there is provided a secondary battery comprising a solid electrolyte and an electrode disposed on the solid electrolyte, A secondary battery is provided, wherein the solid electrolyte is the solid electrolyte described above.
[0011] According to at least one embodiment of the present disclosure, there is provided a method for producing a solid electrolyte substrate in which a base, an adhesive, a first particle portion, and a second particle portion are laminated in this order, the method comprising the steps of: the second particle portion includes solid electrolyte particles; The manufacturing method includes: a preparation step of preparing the base having the adhesive; a first step of disposing first particles on a surface of the adhesive; a second step of applying pressure to the first particles to produce the first particle portion; a third step of disposing second particles on the surfaces of the first particle portions; a fourth step of applying pressure to the second particles to produce the second particle portion and obtain the solid electrolyte base material; The present invention provides a method for producing a solid electrolyte substrate, comprising:
[0012] According to at least one embodiment of the present disclosure, there is provided a method for producing a solid electrolyte substrate in which a base, an adhesive, and a particle portion are laminated in this order, the method comprising the steps of: providing the base with the adhesive; disposing solid electrolyte particles on a surface of the adhesive; applying pressure to the solid electrolyte particles to produce the particle portion and obtain the solid electrolyte base material; A method for producing a solid electrolyte substrate having the following structure is provided. Effect of the Invention
[0013] According to at least one embodiment of the present disclosure, there is provided an easily handled solid electrolyte substrate for obtaining a solid electrolyte having high ionic conductivity and suppressed short circuits. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is an image showing a solid electrolyte substrate. [Diagram 2] FIG. 2 is a conceptual diagram showing a method for producing a solid electrolyte substrate. [Diagram 3] FIG. 2 is a schematic diagram showing an apparatus using rolls in a method for producing a solid electrolyte substrate. [Figure 4] FIG. 2 is a schematic diagram showing an apparatus using a press in a method for producing a solid electrolyte substrate. [Diagram 5] FIG. 2 is a schematic diagram showing an apparatus using rolls in a method for producing a solid electrolyte substrate when the first particles and the second particles are the same. [Figure 6] FIG. 2 is a schematic diagram showing an apparatus using a press in a case where the first particles and the second particles are the same in a method for producing a solid electrolyte substrate. [Figure 7] FIG. 2 is a schematic diagram showing an apparatus using a base on which an adhesive is applied in a method for producing a solid electrolyte substrate. [Figure 8] FIG. 2 is a schematic diagram showing an apparatus using a base on which an adhesive is applied in a method for producing a solid electrolyte substrate. [Figure 9] FIG. 2 is a diagram showing a schematic configuration of a base removing device and a sintering treatment device. [Figure 10] SEM image of the substrate, binarized image. [Figure 11] Graph showing calculated area ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In the present disclosure, the descriptions "XX or more and YY or less" and "XX to YY" expressing a numerical range mean a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, any combination of the upper and lower limits of each numerical range is also disclosed. In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.
[0016] When an inorganic solid electrolyte is used as the electrolyte, it is difficult to obtain a sufficient contact area because the electrolyte comes into contact in a solid state, making it difficult to establish a conductive path at the interface and causing problems such as short circuits. In addition, it is possible to increase the contact area by increasing the amount of solid electrolyte, but this increases the thickness, resulting in a decrease in ionic conductivity (increase in resistance).
[0017] In order to solve the above-mentioned problems, the present inventors have conducted detailed studies on the configuration of the solid electrolyte particles of the solid electrolyte substrate. As a result of the studies, it has been found that the following configuration makes it possible to obtain a solid electrolyte layer that is easy to handle, suppresses short circuits, and improves ion conductivity. That is, the solid electrolyte substrate has a base, a first particle portion elastically held to the base by an adhesive, and a second particle portion including a compact of a solid electrolyte that is stacked and held on the first particle portion.
[0018] This means that the first particle portion, which is elastically retained, and the second particle portion, which is part of the powder compact, each have their own role in constituting the base material. This will be explained with reference to FIG. 1. In FIG. 1, the particle portion (first particle portion) fixed to the base 11 by adhesive has spaces created by the adhesive. In other words, the first particle portion can have a layered structure in which particles are dispersed in the adhesive. On the other hand, the particle portion constituting the powder compact above the first particle portion has less space and is a high-density particle portion (second particle portion) because no adhesive is present.
[0019] As an example of a method for producing a solid electrolyte substrate, there is a method for producing a substrate by pressing a particle part from above a base, in which case a pressing force is applied by the second particle part to the first particle part. In addition, the method is not limited to a method for producing a substrate by pressing, and a pressing force is also applied by the mass of the second particle part to the first particle part. Here, the adhesive may contain, for example, a resin, but is elastically deformable even in a hardened state. Therefore, it is considered that the first particle part fixed to the adhesive spreads slightly like a spring due to the above-mentioned pushing force transmitted by the second particle part, and the first particle part can move against the pushing force. As a result, the first particle part can hold the second particle part as if biting it. It is considered that the space can be reduced at the interface between the first particle part and the second particle part, and the second particle part can be strongly held. At the same time, it is considered that the second particle part becomes a compressed powder state due to the pushing force, and becomes a particle part of a solid electrolyte with high density.
[0020] Therefore, in the present disclosure, "retaining elasticity" refers to a state in which the first particle portion is fixed to the adhesive and is included in the second particle portion by the pushing force transmitted from the second particle portion described above. This refers to a state in which particles are held by biting.
[0021] In the solid electrolyte substrate, the "elasticity retention" of the first particle portion can be confirmed, for example, by the fact that the first particle portion is fixed to, for example, the carbon C component derived from the adhesive in a measurement by BIB-SEM described later, and further by the fact that a compressed powder body of the second particle portion is formed thereon.
[0022] In order to "elastically retain" the first particle portion in the solid electrolyte substrate, as described above, a layer of adhesive is formed on the base, and the first particle portion is formed so as to be dispersed and retained in the adhesive. It is then preferable to laminate a second particle portion including a compact of solid electrolyte particles on the first particle portion. That is, as another aspect of the present disclosure, the solid electrolyte substrate has a base, a layer of adhesive on the base, a first particle portion dispersed and retained in the adhesive, and a second particle portion including a compact of solid electrolyte particles laminated and retained on the first particle portion.
[0023] Furthermore, in the solid electrolyte base material, the fact that the second particle portion is a "compressed powder" can be confirmed by observing a cross section using a BIB-SEM, which will be described later, from the fact that the area ratio, i.e., the density, is high. Preferably, in cross-sectional observation of the solid electrolyte substrate by a scanning electron microscope, the area ratio (%) of the first particle portion is d1, and the area ratio (%) of the second particle portion is d2. It is preferable that d2 is 86% or more. More preferably, d2 is 86 to 96%, and further preferably, 87 to 94%. Incidentally, d1 is preferably 80 to 85%, and more preferably 82 to 85%.
[0024] Furthermore, with the solid electrolyte base material of the present disclosure, only a small amount of adhesive is required to maintain the elasticity of the first particle portion, and during production of the solid electrolyte layer, for example, a low temperature can be used to remove the resin component including the base, making it possible to minimize the effect of density reduction due to the removal.
[0025] In order to produce the above-mentioned solid electrolyte substrate, it is considered important to have a first particle portion that is elastically held to the base by an adhesive and a second particle portion that constitutes a powder compact. In the solid electrolyte substrate having such a configuration, the first particle portion and the second particle portion, especially the second particle portion, are densely packed. Therefore, by manufacturing a solid electrolyte layer using the solid electrolyte substrate of the present disclosure, short circuits are unlikely to occur and ions are easily conducted. In addition, in a secondary battery using such a solid electrolyte layer, the internal resistance is reduced and the output can be improved.
[0026] In the present disclosure, the above-mentioned form is realized by using a solid electrolyte base material in which solid electrolyte particles are arranged on a base having the characteristics of the present disclosure. The solid electrolyte base material can also be used as a material for a secondary battery. In the present disclosure, the electronic conductivity and ionic conductivity are evaluated using an index called "resistance value" for convenience.
[0027] The solid electrolyte substrate, the solid electrolyte layer, and the secondary battery using them, as well as the manufacturing method thereof, are described in detail below. The solid electrolyte substrate of the present disclosure can be used for manufacturing a solid electrolyte. The solid electrolyte can be used for manufacturing a secondary battery. The following description is given by taking a solid electrolyte substrate using solid electrolyte particles as an example.
[0028] The base may be any material that basically constitutes a solid electrolyte base material. Preferably, the base contains a resin. By using a base formed of an organic material such as a resin, it is possible to easily remove the base by heating in the manufacturing process of the solid electrolyte layer described later.
[0029] The resin contained in the material of the base is not particularly limited, and examples thereof include polyesters such as polyethylene (PE), polypropylene (PP) and polyethylene terephthalate (PET), as well as polyamides such as nylon, etc. Among these, it is preferable that the base contains PET from the viewpoints of the decomposition temperature and the low toxicity of gas generated during thermal decomposition. The thickness of the base is preferably 1 to 50 μm, more preferably 1 to 20 μm, and further preferably 2 to 10 μm.
[0030] The adhesive is preferably a resin having adhesive and tackiness. It is preferable that the adhesive is provided on a part or the whole surface of the base. Since the adhesive is intended to maintain the elasticity of the base and the first particle portion, the adhesive is not particularly limited, but a method of applying the adhesive to the surface of the base is preferable.
[0031] The adhesive is not particularly limited, and known adhesives can be used. The adhesive includes, for example, a resin. The adhesive preferably has adhesiveness. Adhesiveness refers to a property that allows temporary adhesion. The adhesiveness makes it easier to maintain the elasticity of the first particles. The adhesive may be, for example, an acrylic adhesive, a rubber adhesive, or a silicone adhesive, or may be a thermoplastic resin or a photocurable resin whose adhesive strength changes due to disturbances such as heat or light. It is more preferable that the adhesive is an adhesive. It is even more preferable that the adhesive is at least one selected from the group consisting of an acrylic adhesive, a rubber adhesive, and a silicone adhesive.
[0032] The solid electrolyte substrate has, for example, a base, a first particle portion held on the base by an adhesive, and a second particle portion including a compact of solid electrolyte particles stacked and held on the first particle portion.
[0033] The thickness of the adhesive (thickness after curing) is not particularly limited, but is preferably 0.1 to 10 μm, more preferably 0.5 to 5 μm, and even more preferably 0.5 to 3 μm.
[0034] The particles contained in the first particle portion are not particularly limited, but are preferably at least one particle selected from the group consisting of resin particles and solid electrolyte particles. In the case where the particles are those that disappear by heating, they can be easily removed in the manufacturing process of the solid electrolyte layer described later. The particles in this case are preferably made of an organic material, and are not particularly limited, but the particles in the first particle portion may be resin particles.
[0035] The resin particles may be particles of at least one resin selected from the group consisting of polyesters such as polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET), polyacrylic resins, and polyamides such as nylon.
[0036] The particles in the first particle portion may be solid electrolyte particles that do not disappear when heated and form a solid electrolyte layer. The solid electrolyte particles are not particularly limited, and any ion-conductive solid that is normally used in all-solid-state batteries may be used. The solid electrolyte particles may be at least one particle selected from the group consisting of Li-B oxide-based solid electrolyte particles, Li-Yb oxide-based solid electrolyte particles, Nasicon-type solid electrolyte particles (LiAlTi(PO4)3, LiAlGe(PO4)3, etc.), and Li-PO-based solid electrolyte particles (Li3PO4, LiPON (particles in which some of the O in Li3PO4 is replaced with N), etc.).
[0037] Preferably, the solid electrolyte particles include oxide-based solid electrolyte particles. Among these, Li-B oxide-based solid electrolyte particles and Li-Yb oxide-based solid electrolyte particles can be sintered at a relatively low temperature (700° C. or lower), and therefore, it is possible to suppress the reaction with the positive electrode active material particles during sintering in the preparation of an integrated battery, and it is easy to maintain ionic conductivity. For this reason, it is preferable that the solid electrolyte particles include at least one particle selected from the group consisting of Li-B oxide-based solid electrolyte particles and Li-Yb oxide-based solid electrolyte particles.
[0038] The solid electrolyte particles may be commercially available products or may be prepared separately as materials. Examples of the Li-B oxide-based solid electrolyte particles include Li3BO3 (manufactured by Toshima Manufacturing Co., Ltd.) and particles in which part of the O in Li3BO3 is replaced with C. Examples of the Li-Yb oxide-based solid electrolyte particles include compounds described in JP-A-2022-130301, such as Li 5.9 Yb 0.81 La 0.09 Zr 0.1 (BO3)3, etc. can be used. These solid electrolyte particles may be made amorphous in advance by planetary ball milling or the like.
[0039] The particles in the second particle portion include solid electrolyte particles. The solid electrolyte particles are not particularly limited, and an ion-conductive solid commonly used in all-solid-state batteries can be used. The solid electrolyte particles used in the first particle portion shown above can be used.
[0040] In the cross-sectional observation of the solid electrolyte substrate by a scanning electron microscope, when the average of the area ratio (%) of the first particle portion is d1 and the average of the area ratio (%) of the second particle portion is d2, it is preferable that d1 and d2 are different. Further, it is preferable that d1 and d2 satisfy d1 < d2. By making d1 and d2 different in this way, the gas generated from the adhesive during the removal of the resin by heating or the like can easily escape (preferably through the first particle portion). Therefore, cracks are less likely to occur in the solid electrolyte, and short circuits are more easily suppressed.
[0041] The area ratio of the first particle portion and the second particle portion is obtained from a two-dimensional image obtained by processing a cross-section in the stacking direction of the base, the first particle portion, and the second particle portion of the solid electrolyte substrate with a broad ion beam (BIB) using Ar and observing the cross-section by a scanning electron microscope method. Also, the location of the adhesive can be measured by an EDX method that detects and spectroscopically analyzes characteristic X-rays generated by electron beam irradiation.
[0042] In this specification, the first particle portion indicates the particle portion held by the adhesive by the above cross-sectional observation by the EDX method together with SEM observation. The first particle portion has a distribution in the height (Y direction according to the image), and the position up to the maximum height of the particles held by the adhesive is defined as the first particle portion. Therefore, the second particle portion becomes a portion clearly without adhesive by the above cross-sectional observation by the EDX method.
[0043] The difference between d1 and d2 (preferably d2-d1) is preferably statistically significant. The difference between d1 and d2 (preferably d2-d1) is preferably 2% or more. By doing so, the first particle portion is more likely to be elastically maintained by the adhesive, and the second particle portion is more likely to be fixed by the first particle portion. As a result, the second particle portion, which is a solid electrolyte particle, can be formed with a sufficiently high density, and the ion conductivity can be further improved.
[0044] The difference between d1 and d2 (preferably d2-d1) is preferably 2 to 10%, more preferably 3 to 7%. The difference between d1 and d2 can be increased by increasing the thickness of the adhesive, and can be decreased by decreasing the thickness of the adhesive or decreasing the amount of change in the adhesive relative to pressure.
[0045] The thickness of the first particle portion is preferably 1 to 20 μm, more preferably 2 to 15 μm, and further preferably 3 to 10 μm. The thickness of the second particle portion is preferably 10 μm or more and less than 100 μm, more preferably 20 to 90 μm, and further preferably 25 to 80 μm. The total thickness of the first particle portion and the second particle portion is preferably less than 100 μm. By being in the above range, the resistance of the solid electrolyte after sintering can be reduced. The total thickness of the first particle portion and the second particle portion is preferably 20 μm or more and less than 100 μm, more preferably 25 to 90 μm, and further preferably 30 to 80 μm.
[0046] The thickness of the adhesive, the thickness of the first particle portion, and the thickness of the second particle portion in the solid electrolyte substrate can be measured by observation with a BIB-SEM. The arithmetic average value of 10 arbitrary points is used.
[0047] <Method of manufacturing solid electrolyte substrate 1> An example of a method for producing a solid electrolyte substrate will be described in detail below with reference to Fig. 2. A solid electrolyte substrate using solid electrolyte particles for the first particle portion and the second particle portion will be described below as an example, but the substrate can also be produced in the same manner when resin particles are used for the first particle portion.
[0048] A method for producing a solid electrolyte substrate in which a base, an adhesive, a first particle portion, and a second particle portion are laminated in this order preferably includes the following steps (1) to (5). (1) A preparation step of preparing a base with an adhesive. (2) A first step (S101 in FIG. 2) of disposing first particles on a surface of an adhesive. (3) A second step (S102 in the figure) of applying pressure to the first particles to produce first particle portions. (4) A third step (S103 in the figure) of disposing second particles on the surfaces of the first particle portion. (5) A fourth step (S104 in the figure) of applying pressure to the second particles to produce second particle portions and obtain a solid electrolyte substrate.
[0049] (preparation process) In the preparation step, a base provided with an adhesive is prepared. In this disclosure, the term "provided with an adhesive" refers to an adhesive being provided on a part or the entire surface of the base. The base may be any of the bases described above. The method for providing the adhesive is not particularly limited, but a method of coating the surface of the base with adhesive is preferred.
[0050] The adhesive is not particularly limited, and known adhesives can be used. For example, it may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, or a thermoplastic resin or a photocurable resin whose adhesive strength changes due to disturbances such as heat or light. The adhesive is as described above, and an adhesive is preferable. An adhesive having adhesive properties makes it easier to maintain elasticity.
[0051] (Steps 1, 2, 3, and 4) The first step is a step of arranging the first particles on the surface of the adhesive on the base. It is preferable to arrange the particles so that the adhesive is not exposed. The thickness of the first particles is preferably 1 to 20 μm, more preferably 2 to 15 μm, and further preferably 3 to 10 μm.
[0052] The second step is a step of fixing the first particles with an adhesive so that the first particles are elastically maintained. The pressure is not particularly limited as long as the first particles can be elastically maintained. A certain degree of force can easily hold the first particles. The pressure is preferably 5 to 300 kPa, and more preferably 100 to 300 kPa.
[0053] The third step is a step of disposing the second particles on the first particle portion. The second particles may be disposed to such an extent that a green compact can be formed. The thickness of the second particles is preferably 10 μm or more. The thickness is less than 100 μm, more preferably 20 to 90 μm, and further preferably 25 to 80 μm.
[0054] The fourth step is a step of stacking and holding the second particle part on the first particle part by applying pressure in the same manner as in the second step, thereby producing a green compact made of the second particle part. It is sufficient to apply pressure to the extent that a green compact is formed. The pressure in the fourth step is not particularly limited, but is preferably 5 to 300 kPa, and more preferably 100 to 300 kPa.
[0055] <Method of manufacturing electrolyte base material 2> When the same solid electrolyte particles are used for the first particles and the second particles, after the first step of arranging the solid electrolyte particles on the surface of the adhesive part, the second and third steps are not required, and only the fourth step may be performed. As a result, a first particle part is formed by a part of the solid electrolyte particles being elastically held to the base by the adhesive, and further a second particle part including a powder compact stacked and held on the first particle part can be formed.
[0056] That is, the method for producing a solid electrolyte substrate 2 in which a base, an adhesive, and solid electrolyte particles are laminated in this order may include the following steps (1) to (3). (1) A preparation step of preparing a base with an adhesive. (2) disposing solid electrolyte particles on the surface of the adhesive; (3) A step of applying pressure to the solid electrolyte particles to produce particle portions of the solid electrolyte particles and obtain a solid electrolyte substrate.
[0057] Moreover, the method for producing a solid electrolyte substrate 2 in which the base, the adhesive, and the solid electrolyte particles are laminated in this order preferably includes the following steps (1) to (3). (1) A preparation step of preparing a base with an adhesive. (2) disposing solid electrolyte particles on the surface of the adhesive; (3) A step of applying pressure to the solid electrolyte particles to produce a first particle portion held by the adhesive and a second particle portion including a compact of the solid electrolyte particles, thereby obtaining a solid electrolyte substrate.
[0058] The thickness of the solid electrolyte particles is preferably 10 μm or more and less than 100 μm, more preferably 20 to 90 μm, and further preferably 25 to 80 μm. The pressure in the step (3) is preferably 5 to 300 kPa, and more preferably 100 to 300 kPa.
[0059] The particle size of the first particles is not particularly limited, but for example, the cumulative 10% particle size (r10) in the volumetric particle size distribution of the primary particles is preferably 0.1 to 10.0 μm, more preferably 1.0 to 7.0 μm. The cumulative 50% particle size (r50) in the volumetric particle size distribution of the primary particles is preferably 0.5 to 20.0 μm, more preferably 2.0 to 10.0 μm. Furthermore, the cumulative 90% particle size (r90) in the volumetric particle size distribution of the primary particles is preferably 2.0 to 20.0 μm, more preferably 3.0 to 15.0 μm.
[0060] The second particles are solid electrolyte particles. For example, the above-mentioned solid electrolyte particles can be used as the second particles.
[0061] The particle size of the primary particles of the second particles is not particularly limited. For example, the cumulative 10% particle size (r10) in the volume-based particle size distribution of the primary particles of the second particles is preferably 0.1 to 10.0 μm, more preferably 1.0 to 7.0 μm. Furthermore, the cumulative 50% particle size (r50) in the volume-based particle size distribution of the primary particles is preferably 0.5 to 20.0 μm, more preferably 2.0 to 10.0 μm. Furthermore, the volume of the primary particles The cumulative 90% particle size (r90) in the standard particle size distribution is preferably 2.0 to 20.0 μm, and more preferably 3.0 to 15.0 μm. The ratio of the first particle size to the second particle size is not particularly limited.
[0062] [Solid electrolyte base material manufacturing equipment 1] FIG. 3 is a diagram showing a schematic configuration of a solid electrolyte substrate manufacturing apparatus 1. The solid electrolyte substrate manufacturing apparatus 1 is an apparatus for forming a first particle portion 14 and a second particle portion 12 on a base 11. The solid electrolyte substrate manufacturing apparatus 1 has a storage container 21 for storing and supplying the base 11, and a belt device 22 for transporting the base 11. The solid electrolyte substrate manufacturing apparatus 1 also has a liquid application device 201 for disposing a liquid for providing an adhesive on the base 11. The belt device is provided with a first particle application device 202 for stacking first particles and a particle fixing device 25, following the liquid application device 201 from the upstream side. And, a second particle application device 203 for stacking second particles and a particle fixing device 26 are provided downstream of the liquid application device 201.
[0063] As the liquid applying device 201, a device that ejects liquid by an inkjet method or a device that applies liquid can be used, but a plate-based method such as a flexographic plate can also be used. Among them, it is preferable to use a device that ejects liquid by an inkjet method as the liquid applying device.
[0064] As a device for discharging liquid by the inkjet method, devices using various discharging methods, such as a thermal type, a piezoelectric type, an electrostatic type, and a continuous type, can be used.
[0065] The liquid for providing the adhesive applied by the liquid applying device 201 may be water-based or oil-based as long as it contains a material capable of holding the first particles capable of forming the first particle portion. The liquid is appropriately selected, for example, by selecting a material that does not react with the first particles. The liquid applying device 201 may also form a pattern using a plurality of types of liquid. For example, the liquid applying device 201 may apply two types of liquid that react with the substrate 11 to increase adhesion. Examples of materials to which the first particles can be attached include resins such as acrylic resins.
[0066] The first particle applying device 202 places a powder containing first particles on the base 11 on which the adhesive is laminated. As a result, the first particles are fixed by the material on the base 11.
[0067] The means for applying the powder by the first particle applying device 202 may be a means for spraying or sprinkling the powder toward the base 11. The first particle applying device 202 may further include a means for removing the first particles that have not been fixed to the base 11 by means of vibration, centrifugation, air blowing, suction, or the like.
[0068] The particle fixing device 25 has pressure rollers 223c and 223d, and the pressure roller 223d rotates by being driven. At least one of the pressure rollers 223c and 223d is preferably a soft roller having an elastic layer on its surface, for example, a soft roller having an elastic layer of silicone rubber or fluororubber on the surface of a stainless steel core metal. In addition, a heater (not shown) may be built in at least one of the pressure rollers 223c and 223d.
[0069] The base 11 is transported by a belt device to a pressure section between the pressure rollers 223c, 223d. When the base material 11 is pressed by the pressure rollers 223c, 223d, the first particles arranged on the surface of the adhesive on the base are held by the adhesive on the base to form a first particle section. At this time, the above-mentioned heater may be used to make it easier to rearrange the particles of the adhesive on the base. Also, a heat source is provided upstream of the particle fixing device 25 to heat the adhesive on the base material. The pressure applied by the pressure roller is preferably in the above-mentioned range.
[0070] The base 11 on which the first particle portion 14 is placed is transported by a belt device to the second particle applying device 203. The second particle applying device 203 places powder containing second particles on the base 11 on which the first particle portion 14 is located.
[0071] Next, the base 11 to which the second particles have been applied is transported to a pressure section between the pressure rollers 224c and 224d by the belt device 22. The particle fixing device 26 has the pressure rollers 224c and 224d, similar to the particle fixing device 25, and the pressure roller 224d is driven to rotate. When the base material 11 is pressed by the pressure rollers 224c and 224d, the second particle portion 12 is formed by the second particles on the first particle portion 14 on the base.
[0072] The solid electrolyte substrate manufacturing apparatus 1 may further include a drying device that evaporates at least a part of the liquid applied by the liquid application device 201 to control the amount, thickness, and the like of the material on the base 11. This drying device may be provided downstream of the liquid application device 201. The material on the base after drying may be a liquid, a liquid containing solids, or only solids.
[0073] Since the pressure rollers 223c and 224c come into contact with the particles on the base, it is preferable to coat the surfaces with a material with good releasability, such as fluorine, to suppress adhesion of particles. A cleaning mechanism for removing particles adhering to the pressure rollers 223c and 224c may be provided. It is more preferable to apply pressure while the particle layer is covered with a protective material (not shown).
[0074] In this case, the protective material used is preferably a material with good releasability, and if it is a resin, it is preferably a fluorine sheet, if it is a metal, it is preferably a nichrome foil, etc. When a protective material is used, a removal mechanism (not shown) for removing the protective material is provided downstream of the particle fixing device 25 and upstream of the second particle applying device 203.
[0075] [Solid electrolyte base material manufacturing equipment 2] 4 is a diagram showing a schematic configuration of the solid electrolyte substrate manufacturing apparatus 2. The solid electrolyte substrate manufacturing apparatus 2 is an apparatus for forming a solid electrolyte layer 12 on a base 11, similar to the solid electrolyte substrate manufacturing apparatus 1, and includes a storage container 21 for storing and supplying the base 11, and a belt device 22 for transporting the base 11. The solid electrolyte substrate manufacturing apparatus 2 also includes a liquid applying device 201 for applying a liquid for providing an adhesive portion on the base 11. The belt device includes, from the upstream side, the liquid applying device 201, a first particle applying device 202, a particle fixing device 301, and a second particle applying device 203 and a particle fixing device 302, which are arranged downstream of the liquid applying device 201.
[0076] The step of fixing the particles is different from that of the solid electrolyte substrate manufacturing apparatus 1 in that the particles are fixed by pressing, but the other configurations are the same. The pressure during pressing is also preferably in the range described above. The pressure is preferably 5 kPa or more, and although it depends on the strength of the base, when a PET film is used, it is preferably 300 kPa or less to prevent damage. More preferably, it is 100 to 300 kPa.
[0077] [Other solid electrolyte substrate manufacturing equipment] 5 and 6 are diagrams illustrating a solid electrolyte substrate manufacturing apparatus when the same particles are used for the first particles and the second particles. Since the same particles are used for both, only one particle applying device 202-2 is required. In addition, in FIG. 5, the particles are fixed by a pressure roller, and in FIG. 6, the particles are fixed by a press.
[0078] In addition, in Figures 7 and 8, a solid electrolyte substrate is used that originally had adhesive applied to the base. This is a manufacturing device. Since adhesive is applied to the base 11 in advance, a protective film is attached to the base. The protective film is removed by a protective film removing mechanism 401, and the device moves to the next process.
[0079] In the solid electrolyte substrate, the coverage of the base surface by the solid electrolyte particles is preferably 60 area % or more, more preferably 70 area % or more, and even more preferably 80 area % or more.
[0080] In the present disclosure, the coverage rate of the base surface refers to the ratio (area %) of the area covered by the solid electrolyte particles to the entire area of the base surface. The coverage rate of the base surface by the solid electrolyte particles can be measured by photographing the area where the particle layer is formed using an optical microscope from the vertical direction of the substrate, and calculating the area ratio of the area covered by the solid electrolyte particles using image processing software. The details of the measurement method will be described later.
[0081] The upper limit of the coverage is not particularly limited, but is preferably 99% or less by area, and more preferably 98% or less by area. For example, the coverage of the resin substrate surface by the solid electrolyte particles is preferably 60 to 99% by area, 70 to 99% by area, or 80 to 99% by area. It is preferably in the range of 60 to 98% by area, 70 to 98% by area, or 80 to 98% by area. When the coverage rate is within the above range, a dense particle layer is formed on the base, and the denseness of the particles in the solid electrolyte layer can be improved, resulting in further improved ion conductivity.
[0082] <Method of manufacturing solid electrolyte layer> Hereinafter, with reference to FIG. 9, an example of a method for producing a solid electrolyte layer will be described in detail. The method for producing the solid electrolyte layer includes the following two steps (step A and step B). (Step A) The base is removed from the solid electrolyte substrate to form a solid electrolyte integrated body. (Step B) Sintering the solid electrolyte unit to obtain a solid electrolyte layer That is, the solid electrolyte layer produced by the step of removing the base to obtain an integrated body and the step of sintering the integrated body can be used as the solid electrolyte. Each step of the method for producing the solid electrolyte layer will be described in detail below.
[0083] (Solid electrolyte layer manufacturing method - Process A) Step A is a step of forming a solid electrolyte integral from a solid electrolyte substrate, and is a step of removing the base. When resin particles are used for the first particle portion, it is preferable that the resin components of the resin particles and the resin components of the adhesive are also removed together with the base. Therefore, the base to be removed here is the resin components including the base. It is preferable to remove the base by heating. FIG. 9 is a diagram showing a schematic configuration of a sintering treatment device. The sintering treatment device has a conveying device 41 that conveys the solid electrolyte substrate 15, and a heating furnace 42 that heats the laminate 15. A plurality of solid electrolyte substrates may be laminated before step A. The number of layers is not particularly limited and may be determined according to the desired capacity of the solid electrolyte.
[0084] The conveying device 41 receives the produced solid electrolyte substrate 15 and conveys it to the heating furnace 42. The conveying device 41 is preferably a device capable of conveying the solid electrolyte substrate 15. Examples of devices capable of conveying the solid electrolyte substrate 15 include a belt conveyor, a roller, and a robot arm.
[0085] The heating furnace 42 is a furnace for heating the solid electrolyte substrate 15. The heating furnace 42 has a heating means 421, a pressurizing means 422, and an atmosphere adjusting means 423. A firing furnace used for firing ceramics or the like can be used as the heating furnace 42. The pressurizing means 422 pressurizes the laminate 15 being heated in the heating furnace 42, and pressurizes the laminate 15 before and after heating.
[0086] In addition, it is preferable that the pressurizing means 422 has a pressurizing portion for pressurizing the laminate 15 formed of a porous material that allows easy passage of gas. The atmosphere adjusting means 423 has an atmosphere gas supplying means 423a and a pressure reducing means 423b, and adjusts the atmosphere gas in the processing space of the heating furnace 42. The atmospheric gas that can be used includes an oxidizing atmosphere (O2), an inert atmosphere (Ar, N2, etc.) and a reducing atmosphere (Ar-H2), but sintering may be performed in air.
[0087] When sintering, it is preferable to heat at a temperature equal to or higher than the thermal decomposition temperature of the base 11 in the solid electrolyte substrate, and it is preferable to heat at a temperature lower than the thermal decomposition temperature of each particle layer in the solid electrolyte substrate. The temperature at which the solid electrolyte substrate is heated is preferably 200°C or higher and 1000°C or lower, and more preferably 400°C or higher and 800°C or lower. It is preferable to maintain the sintering temperature for 30 minutes or more, and more preferably for 1 hour or more. It is sufficient to heat for a time that allows the base to be removed, and the upper limit is not particularly limited, but it is preferably 3 hours or less, more preferably 2 hours or less.
[0088] The thermal decomposition temperature is the temperature at which the weight of the material starts to decrease when the temperature is gradually increased in the heating atmosphere in the sintering apparatus. Therefore, by heating the solid electrolyte substrate at a temperature equal to or higher than the thermal decomposition temperature of the substrate, the substrate of the solid electrolyte substrate can be decomposed and removed.
[0089] The heating temperature is preferably equal to or higher than the thermal decomposition temperature of the base, but it is preferable to heat at a temperature higher than the thermal decomposition temperature. Specifically, when the temperature is increased from room temperature (25°C) at a rate of 5°C / min in an atmosphere (typically air) during heating in a sintering treatment device and thermogravimetric analysis is performed, it is preferable to heat at a temperature equal to or higher than the temperature at which the mass becomes 70% by mass of the initial mass. Specifically, for example, 385°C or higher is preferable.
[0090] Similarly, when a thermogravimetric analysis is performed, it is more preferable to heat the material at a temperature equal to or higher than the temperature at which the mass is reduced to 50% by mass of the initial mass, and it is even more preferable to heat the material at a temperature equal to or higher than the temperature at which the mass is reduced to 20% by mass of the initial mass. Specifically, for example, the temperature is preferably 400° C. or higher, and more preferably 450° C. or higher. This can shorten the time required to remove the base and increase the removal rate of the base. In this way, when the sintering apparatus removes the base by heating, it is preferable that the solid electrolyte particles have a higher thermal decomposition temperature than the base.
[0091] When a plurality of solid electrolyte substrates are laminated, the sintering apparatus preferably removes at least a portion of the base in the solid electrolyte substrate by heating to provide a portion where the particles of the upper and lower laminated solid electrolyte layers come into contact. Therefore, it is preferable to remove 90% by mass or more of the base in the solid electrolyte substrate 15, more preferably remove 95% by mass or more, and even more preferably remove 97% by mass or more. At this time, it is preferable that the base is burned or gasified and released to the outside as gas. At this time, it is preferable that the gasified by pyrolysis is released to the outside of the apparatus.
[0092] The sintering apparatus preferably exhausts the released gas to the outside of the heating furnace 42 by the pressure reducing means 423b. The base can be burned and removed by creating an oxidizing atmosphere, i.e., an atmosphere containing oxygen gas such as air, inside the heating furnace 42 by the atmospheric gas supplying means 423a or the like. On the other hand, depending on the solid electrolyte particles, decomposition or composition change may occur due to sintering in an oxidizing atmosphere. In such cases, sintering in an inert atmosphere (Ar, N2, etc.) or a reducing atmosphere (Ar-H2) is preferable.
[0093] When the base is gasified by pyrolysis from the solid electrolyte substrate 15 and released as gas, the solid The particle layer in the solid electrolyte substrate may be pushed up and the shape may change. Therefore, when heating in the heating furnace 42, the solid electrolyte substrate 15 may be pressurized by the pressurizing means 422 before or during heating.
[0094] (Solid electrolyte layer manufacturing method - Process B) In step B, the base is removed and the resulting solid electrolyte integrated body is sintered to sinter and bond the solid electrolyte particles together to produce a solid electrolyte layer. At this time, the solid electrolyte is heated to a sintering temperature that corresponds to the type of solid electrolyte. If a material with high thermal stability at high temperatures is used for the base material, there is no particular effect, but if a material that becomes unstable when exposed to heat is used, it is better to leave only the solid electrolyte integrated body before step B. If a resin film is used for the base, it is considered to have been thermally decomposed in step A, so it can proceed directly to step B.
[0095] Alternatively, pressure may be applied using a separate pressure device after removing the base before step B. Specific pressure application methods are preferably vacuum degassing, isostatic pressure application, or a general hydraulic press or roller press. Among these, it is preferable to apply pressure using a combination of vacuum degassing and isostatic pressure application. The pressure is preferably 5 MPa to 500 MPa, which fills the voids in the solid electrolyte unit from which the base has been removed, improving the density and strength of the three-dimensional object. A solid electrolyte layer can be produced by a production method including the above-mentioned steps. With this configuration, the resistance value of the solid electrolyte can be reduced.
[0096] <Secondary battery manufacturing method> The secondary battery can be manufactured by using the solid electrolyte layer prepared by the above method and a separate current collector or a positive electrode or a negative electrode formed by another means. The secondary battery includes at least the above-mentioned solid electrolyte layer and, if necessary, electrodes and current collectors.
[0097] The secondary battery has a laminate of an electrode, a current collector, and a solid electrolyte layer. The laminate may be packaged with an aluminum laminate film or the like as necessary, and molded and pressed to produce a secondary battery. That is, the method for producing a secondary battery may include a step of laminating the electrode, the current collector, and the solid electrolyte layer. The above-mentioned solid electrolyte layer may be used as the solid electrolyte.
[0098] The method for producing a secondary battery may include a step of preparing a solid electrolyte layer by a method for producing a solid electrolyte layer, and a step of providing the above-mentioned solid electrolyte layer adjacent to an electrode. The method may also include a step of providing the electrode and the solid electrolyte layer adjacent to the electrode together. That is, the electrode and the solid electrolyte layer may be prepared in separate steps, or may be prepared together in the same step.
[0099] Here, the other means for forming the electrodes is a known means, for example, forming positive electrode material particles and negative electrode material particles into pellets using a uniaxial pressurizing device or the like, and sintering them in an electric furnace, etc. Sheets, etc. may also be used.
[0100] The manufactured components can be stacked in the order of a positive electrode current collector, a positive electrode, a solid electrolyte layer, a negative electrode, and a negative electrode current collector to form a secondary battery. For example, these stacks can be packed in a laminate film to form a laminated secondary battery, or packed in a coin case to form a coin-type secondary battery.
[0101] The particles constituting the positive electrode, solid electrolyte, and negative electrode may have different suitable temperatures and atmospheres during sintering. When handling such materials, it is preferable to manufacture the positive electrode, solid electrolyte, and negative electrode separately and assemble them into a battery. When using lithium metal or indium as the negative electrode, the negative electrode is used as a metal foil and is sintered by a vacuum process such as sputtering. It is preferable that the lithium metal is formed into a current collector or electrolyte. Since lithium metal has a strong reducing power, it is easily decomposed depending on the type of solid electrolyte. In that case, a buffer layer may be provided between the electrode and the solid electrolyte. It is preferable to use a polymer electrolyte or the like as the buffer layer.
[0102] The secondary battery can also be manufactured as a three-dimensional object by forming a laminate including two or more of a positive electrode current collector, a positive electrode, a solid electrolyte layer, a negative electrode, and a negative electrode current collector.
[0103] For example, each substrate is made of a respective particle layer. That is, a positive electrode current collector substrate, a positive electrode substrate, a solid electrolyte substrate, a negative electrode substrate, and a negative electrode current collector substrate. Each substrate may contain multiple types of particles (positive electrode active material particles and solid electrolyte particles in the case of a positive electrode substrate), or may contain only a single type of particle.
[0104] The negative electrode substrate is formed of a particle layer containing at least negative electrode active material particles. The current collector substrate is formed of a particle layer containing at least conductive particles. These substrates are laminated in the order of a positive electrode current collector substrate, a positive electrode substrate, a solid electrolyte substrate, a negative electrode substrate, and a negative electrode current collector substrate using a lamination unit or the like to produce a laminate, and a secondary battery can be manufactured by removing resin components from the base and carrying out post-treatment. Furthermore, a bipolar type secondary battery can also be manufactured by laminating electrode substrates on both sides of the current collector substrate. EXAMPLES
[0105] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. In the following examples, unless otherwise specified, the parts are based on parts by weight.
[0106] Specifically, a solid electrolyte substrate was produced using the systems shown in Figures 4 and 8.
[0107] Example 1 In Example 1, the system shown in Fig. 4 was used. A 3 μm polyester (PET) sheet (Lumirror, Toray) was used as the base. An acrylic adhesive (T-50, Toagosei Co., Ltd.) was applied to the base as the adhesive so that the thickness would be 1 μm after drying. The first particles were polyacrylic resin particles (MV1002, manufactured by Nippon Shokubai) of 2 μm in size, and were applied so that the thickness of the first particle portion was 5 μm. The pressing condition after applying the first particles was set to 250 kPa. The second particle is Li 1.5 Al 0.5 Ge 1.5 P3O 12 (hereinafter, also referred to as LAGP) powder was applied so that the thickness of the second particle portion became 70 μm. After the second particles were applied, the pressing condition was set to 250 kPa to obtain a solid electrolyte substrate. Then, using the system shown in Fig. 9, the resin components of the base, adhesive, and resin particles were removed from the obtained solid electrolyte substrate by heating to produce a solid electrolyte integrated body, which was then pressed and sintered again to obtain a solid electrolyte layer. The heating for removing the base was performed in an air sintering atmosphere at a temperature of 500°C (maintained for 1 h). Sintering to produce a solid electrolyte layer was performed at 850°C.
[0108] Example 2 The same base and adhesive as those in Example 1 were used. The same LAGP was used for the first particles and the second particles. Therefore, the solid electrolyte substrate was produced using the system in FIG. 8. The pressing conditions were set to 250 kPa. In addition, the total thickness of the first particle portion and the second particle portion was set to the value shown in Table 1. The other conditions were the same as those in Example 1.
[0109] Example 3 The base and adhesive were the same as those used in Example 1. The first and second particles were Li 5.9 Yb 0.81 La 0.09 Zr 0.1 (BO3)3 (manufactured by Canon Inc.; hereinafter, LYb The other conditions were the same as in Example 2. The conditions for removing the base are shown in Table 1.
[0110] Example 4 The base and adhesive used were the same as those in Example 1. The first particles and the second particles used Li3BO3 (hereinafter also referred to as LBO). The other conditions were the same as those in Example 2. The conditions for removing the base are shown in Table 1.
[0111] Example 5 The base and adhesive were the same as those used in Example 1. The first and second particles were Li7La3Zr2O 13 (hereinafter, also referred to as LLZ) was used. The other conditions were the same as in Example 2. The conditions for removing the base are shown in Table 1.
[0112] Example 6 The same base and adhesive as in Example 1 were used. LYbBO was used for the first and second particles. Unlike Example 3, the total thickness of the first and second particle portions was adjusted to 30 μm. The other conditions were the same as in Example 2. The conditions for removing the base are shown in Table 1.
[0113] Comparative Example 1 The same base and adhesive as in Example 1 were used. LAGP was used for the first and second particles. The total thickness of the particle portion was adjusted to 5 μm. The other conditions were the same as in Example 2. The conditions for removing the base are shown in Table 1. In Comparative Example 1, since the particle portion was thin, the second particle portion was not formed.
[0114] Comparative Example 2 The base and adhesive used were the same as in Example 1. LYbBO was used for the first and second particles. The total thickness of the particle portion was adjusted to 5 μm. The other conditions were the same as in Example 2. The conditions for removing the base are shown in Table 1. In Comparative Example 2, since the particle portion was thin, the second particle portion was not formed.
[0115] Comparative Example 3 A solid electrolyte substrate was obtained by adjusting the total thickness of the particles to 70 μm using only LAGP without using a base or adhesive. The pressing conditions were set to 12000 kPa. The rest were the same as in Example 2.
[0116] Comparative Example 4 The total thickness of the particle part was adjusted to 70 μm using only LYbBO without using a base or adhesive. The pressing conditions were set to 12000 kPa. The rest were the same as in Example 3.
[0117] Comparative Example 5 The same base as in Example 2 was used, but no adhesive was used. LAGP particles were used. The pressing conditions were set to 250 kPa. The other conditions were the same as in Example 2. Therefore, in Comparative Example 5, the first particle portion was not formed, and only a green compact by LAGP was formed on the base.
[0118] Comparative Example 6 The base and adhesive were the same as those in Example 2. LAGP particles were used. No second particles were used, and the adhesive was heated at 250 kPa so that the thickness of the adhesive with the first particles dispersed therein was 70 μm. The pressing was performed at 100 Pa. The other conditions were the same as those in Example 2. Therefore, in Comparative Example 6, the second particle portion was not formed.
[0119] Example 7 The base and adhesive used were the same as those in Example 1. LYbBO was used as the particles. The total thickness of the first particle portion and the second particle portion was adjusted to 150 μm. The conditions for removing the base and the like are shown in Table 1. The other conditions were the same as those in Example 2.
[0120] Comparative Example 7 Without using a base and an adhesive, the first particles and the second particles were made of LYbBO. The total thickness of the particle parts was adjusted to 150 μm to obtain a solid electrolyte substrate. The sintering conditions and the like are shown in Table 1. The pressing conditions were set to 12000 kPa. The rest were the same as in Example 3.
[0121] [Table 1] Regarding the thickness, only the total thickness is described for the example fabricated using the system of FIG. 8.
[0122] Table 2 shows the evaluation results of the examples, comparative examples, and reference examples. Also, the evaluation method will be explained.
[0123] · Handleability Evaluation was performed by grasping the center of the flat solid electrolyte substrate (10 mm square) obtained before removing the base (before firing) with tweezers to check if cracks would occur. Those without cracks were rated as A, those without cracks but with warping were rated as B, and those with cracks were rated as C.
[0124] · Measurement of resistance value After removing the base, on the upper and lower surfaces of the sintered body in the shape of a flat plate obtained by sintering, a gold electrode with a diameter of Φ3 was formed using a magnetron sputtering apparatus MSP-10 manufactured by Vacuum Device Co., Ltd. as a sample for performing AC impedance measurement. For the measurement, a potentiostat / galvanostat SI1287A and a frequency response analyzer 1255 manufactured by Solartron Analytical were used. The measurement conditions were room temperature and a frequency range of 1 MHz to 0.1 Hz. The resistance value was calculated from the complex impedance plot obtained by impedance measurement. The resistance value (Ω) obtained by the Z parallel circuit of 10,000 or less was rated as A, those exceeding 10,000 were rated as B, and those with leakage and unable to be measured were rated as C. Also, those with cracks were rated as C because they could not be measured.
[0125] · Difference in area ratio between the first particle layer and the second particle layer It was determined by photographing with BIB-SEM and image processing. <BIB-SEM photographing method> In the determination of the area ratio in the solid electrolyte substrate, BIB-SEM images were used. The BIB-SEM photographing conditions will be explained below. A sample was prepared by vacuum packaging and isostatically pressing a solid electrolyte substrate fabricated on a substrate (Al foil). The sample was cut in the stacking direction of the substrate, first particle part, and second particle part with a wire saw (DWS3400 / wire diameter 170 μm, diamond diameter 30 μm), and the cut surface was cross-sectionally processed with a broad ion beam of Ar (JEOL SM-09010 Cross Section Polisher). The cross-sectional processing conditions were a voltage of 6 kV and a current of 150 to 200 mA. A cross section in the stacking direction was obtained as a BIB-SEM image, and the cross section was observed.
[0126] The cross-section was photographed using an electron microscope (ULTRA55) under the following conditions. Examples of the photographed images (Example 2) are shown in Figures 10A and 10B. Detector: ESB (backscattered electron beam) Observation conditions: Accelerating voltage 3 kV Magnification: 1000x Filter: ESB filter biased to 1500V
[0127] Next, the elements and composition of each particle on the base were analyzed using SEM-EDX (XFlash Detector 630M manufactured by Bruker Corporation) to distinguish between adhesive components and solid electrolyte particles. Specifically, the base, adhesive components, and solid electrolyte particles are identified by analyzing the base and adhesive components using X-ray diffraction (XRD) and identifying the materials that make up the base and adhesive components. After that, the specific elements contained in the solid electrolyte particles are detected and identified using SEM-EDX.
[0128] The first particle portion and the second particle portion are divided as follows. As mentioned above, the position of the particles held by the adhesive up to their maximum height is defined as the first particle portion. Therefore, the position of the adhesive is confirmed by observing the specific elements contained in the adhesive, specifically the carbon C component, using SEM-EDX. Then, particles held by the adhesive are selected, and the position of these up to their maximum height is defined as the first particle portion. Furthermore, the group of particles above the first particle portion that are not in contact with the adhesive is defined as the second particle portion.
[0129] <Calculation method for the ratio of solid electrolyte particles per unit depth> The area ratio of the solid electrolyte particles was detected from the BIB-SEM images taken under the above conditions. First, the BIB-SEM image was normalized to an average brightness of 100 and a standard deviation of ±30. To count the solid electrolyte particles on the base, an image showing only the particle layer on the base was cut out from the normalized image so as to include all particles in the image. An example of the cut-out image is shown in Figure 10A.
[0130] The cut-out image was binarized with a brightness threshold of 70. To remove noise, the area surrounded by white pixels was filled with white, and then the opening process of the morphological transformation was performed. was performed with a kernel size of 3 × 3 pixels to obtain a noise-removed image. An example of the noise-removed image is shown in Figure 10B.
[0131] Next, the top and bottom positions of the white pixels in each vertical column in the image (Figure 10B) obtained above are determined and recorded. The top position of the white pixels in each vertical column is a value that indicates the position of the top surface of the solid electrolyte layer, and the bottom position of the white pixels in each vertical column is a value that indicates the position of the bottom surface of the solid electrolyte layer. In addition, the thickness of the solid electrolyte layer is known to be 70 μm from the SEM image, and the area ratio of the solid electrolyte to the thickness was calculated in 5 μm increments. Specifically, the area ratio of the white part (particle part) was calculated in increments of 300 μm in width and 5 μm in length in a solid electrolyte layer of 300 μm in width and 70 μm in length, as shown in FIG. 10B. Note that d1 and d2 are the average values of the area ratios measured in increments of 300 μm in width and 5 μm in length. The results are shown in Figure 11. From this, the difference in area ratio between the first particle portion and the second particle portion can be obtained. The position 70 μm away (5 μm from the bottom) in Figure 10B is the first particle portion, and the rest is the second particle portion. The area ratio values in the vertical columns in Figure 11 multiplied by 100 are the area % values for d1 and d2. In Figure 11, d1 is 84% and d2 is 88%, and the difference in area ratio (second particle portion - first particle portion) was 4%.
[0132] [Table 2] The difference in area ratio indicates d2-d1.
[0133] Example 8 A secondary battery was produced using the solid electrolyte layer produced in Example 2. A positive electrode was produced using LCO and LAGP based on JP 2019-137060. The negative electrode was made of indium foil (thickness 50 μm). Aluminum foil (thickness 20 μm) was used as the positive electrode current collector. In addition, a copper foil (thickness: 20 μm) was used as the negative electrode current collector. The above-mentioned materials were laminated in the order of positive electrode collector, positive electrode, solid electrolyte layer, negative electrode, and negative electrode collector, and packaged in an aluminum laminate film so that the tab lead for the extraction electrode, which had been welded to the current collector in advance, was placed outside the laminate. The laminate was then molded into a laminate cell type using a vacuum packaging machine, and pressed (196 MPa) using an isostatic pressure device to produce an all-solid-state secondary battery. It was confirmed that the battery could be operated at room temperature.
[0134] Example 9 A secondary battery was produced using the solid electrolyte layer produced in Example 3. A positive electrode was produced using LCO and LYbBO based on JP 2019-137060. Otherwise, an all-solid-state secondary battery was produced in the same manner as in Example 7, and it was confirmed that the battery could be operated at room temperature.
[0135] The present disclosure relates to the following configurations or methods. (Configuration 1) A solid electrolyte substrate used in the production of a solid electrolyte, comprising: The base and a first particle portion elastically held to the base by an adhesive; a second particle portion including a compact of solid electrolyte particles stacked and held on the first particle portion; A solid electrolyte substrate having (Configuration 2) 2. The solid electrolyte substrate according to claim 1, wherein the solid electrolyte particles include oxide-based solid electrolyte particles. (Configuration 3) 3. The solid electrolyte substrate according to claim 1, wherein the total thickness of the first particle portion and the second particle portion is less than 100 μm. (Configuration 4) 4. The solid electrolyte substrate according to any one of claims 1 to 3, wherein the first particle portion includes solid electrolyte particles. (Configuration 5) In observing a cross section of the solid electrolyte substrate using a scanning electron microscope, The solid electrolyte base material according to any one of configurations 1 to 4, wherein d1 is an area ratio (%) of the first particle portion and d2 is an area ratio (%) of the second particle portion, and d1 and d2 are different from each other. (Configuration 6) The d1 and the d2 are d1 <d2を満たす、構成5に記載の固体電解質基材。(Configuration 7) 7. The solid electrolyte substrate according to claim 5, wherein the difference between d1 and d2 is 2% or more. (Configuration 8) 8. The solid electrolyte substrate according to any one of claims 1 to 7, wherein the adhesive has adhesiveness. (Configuration 9) 9. The solid electrolyte substrate according to any one of aspects 1 to 8, wherein the adhesive has a thickness of 0.5 to 5 μm. (Configuration 10) A solid electrolyte substrate used in the production of a solid electrolyte, comprising: The base and a layer of adhesive on the base; a first particle portion dispersed and held in the adhesive; A second particle portion including a compact of solid electrolyte particles stacked and held on the first particle portion. A particle portion; A solid electrolyte substrate having (Configuration 11) 11. A solid electrolyte obtained by removing at least a part of the base from the solid electrolyte substrate according to any one of claims 1 to 10. (Configuration 12) A secondary battery comprising a solid electrolyte and an electrode disposed on the solid electrolyte, 12. A secondary battery, wherein the solid electrolyte is the solid electrolyte according to aspect 11. (Method 13) A method for producing a solid electrolyte substrate in which a base, an adhesive, a first particle portion, and a second particle portion are laminated in this order, comprising the steps of: the second particle portion includes solid electrolyte particles; The manufacturing method includes: a preparation step of preparing the base having the adhesive; a first step of disposing first particles on a surface of the adhesive; a second step of applying pressure to the first particles to produce the first particle portion; a third step of disposing second particles on the surfaces of the first particle portions; a fourth step of applying pressure to the second particles to produce the second particle portion and obtain the solid electrolyte base material; The method for producing a solid electrolyte substrate comprising the steps of: (Method 14) A method for producing a solid electrolyte substrate in which a base, an adhesive, and a particle portion are laminated in this order, comprising the steps of: providing the base with the adhesive; disposing solid electrolyte particles on a surface of the adhesive; applying pressure to the solid electrolyte particles to produce the particle portion and obtain the solid electrolyte base material; The method for producing a solid electrolyte substrate comprising the steps of: (Method 15) 15. The method for producing a solid electrolyte substrate according to method 13 or 14, wherein the adhesive has adhesiveness.
Claims
1. A solid electrolyte substrate used in the production of a solid electrolyte, comprising: The base and a first particle portion elastically held to the base by an adhesive; a second particle portion including a compact of solid electrolyte particles stacked and held on the first particle portion; A solid electrolyte substrate having
2. The solid electrolyte substrate according to claim 1 , wherein the solid electrolyte particles comprise oxide-based solid electrolyte particles.
3. The solid electrolyte substrate according to claim 1 , wherein a total thickness of the first particle portion and the second particle portion is less than 100 μm.
4. The solid electrolyte substrate according to claim 1 , wherein the first particle portion comprises solid electrolyte particles.
5. In observing a cross section of the solid electrolyte substrate using a scanning electron microscope, 2. The solid electrolyte base material according to claim 1, wherein d1 is an area ratio (%) of the first particle portion and d2 is an area ratio (%) of the second particle portion, and d1 and d2 are different from each other.
6. The solid electrolyte substrate according to claim 5 , wherein d1 and d2 satisfy d1<d2.
7. The solid electrolyte substrate according to claim 5 , wherein the difference between d1 and d2 is 2% or more.
8. The solid electrolyte substrate according to claim 1 , wherein the adhesive has adhesive properties.
9. The solid electrolyte substrate according to claim 1, wherein the adhesive has a thickness of 0.5 to 5 μm.
10. A solid electrolyte substrate used in the production of a solid electrolyte, comprising: The base and a layer of adhesive on the base; a first particle portion dispersed and held in the adhesive; a second particle portion including a compact of solid electrolyte particles stacked and held on the first particle portion; A solid electrolyte substrate having
11. A solid electrolyte obtained by removing at least a part of the base from the solid electrolyte substrate according to any one of claims 1 to 10.
12. A secondary battery comprising a solid electrolyte and an electrode disposed on the solid electrolyte, A secondary battery, wherein the solid electrolyte is the solid electrolyte according to claim 11.
13. A method for producing a solid electrolyte substrate in which a base, an adhesive, a first particle portion, and a second particle portion are laminated in this order, comprising the steps of: the second particle portion includes solid electrolyte particles; The manufacturing method includes: a preparation step of preparing the base having the adhesive; a first step of disposing first particles on a surface of the adhesive; a second step of applying pressure to the first particles to produce the first particle portion; a third step of disposing second particles on the surfaces of the first particle portions; a fourth step of applying pressure to the second particles to produce the second particle portion and obtain the solid electrolyte base material; The method for producing a solid electrolyte substrate comprising the steps of:
14. A method for producing a solid electrolyte substrate in which a base, an adhesive, and a particle portion are laminated in this order, comprising the steps of: providing the base with the adhesive; disposing solid electrolyte particles on a surface of the adhesive; applying pressure to the solid electrolyte particles to produce the particle portion and obtain the solid electrolyte base material; The method for producing a solid electrolyte substrate comprising the steps of:
15. The method for producing a solid electrolyte substrate according to claim 13 or 14, wherein the adhesive has adhesiveness.
Citation Information
Patent Citations
Method for producing solid state battery material
JP2012221887A
Method for manufacturing all-solid battery
JP2014212022A